Optimization of extraction process parameters for anti-cancer agent from Solanum Lycopersicum - Amid, Azura; Ahmad, Abdul Aziz; Ahmad Raus, Raha (IIUM Press, 2011)
In the fight against cancer, novel chemotherapeutic agents are continually being sought to complement existing drugs. The optimize extraction process is required to ensure that the maximum yield of anti-cancer agents will be extracted. In this study, three extraction parameters were investigated on their effects toward the anti-cancer activities when applied to MCF-7 breast cancer cell line. A three-factor and three levels Box Behnken design consisting of seventeen experiments was employed including five replicates at the center point. The response variable will be the absorbance reading at 490 nm in terms of percentage cell viability. The design variables were the extraction time (min), extraction agitation speed (rpm) and solvent composition (%, v/v water/methanol). The optimum extraction was found to be 82% methanol, 24 hours and 110 rpm.